2010
DOI: 10.1007/s00296-010-1403-8
|View full text |Cite
|
Sign up to set email alerts
|

Screening and evaluating the mimic peptides as a useful serum biomarker of ankylosing spondylitis using a phage display technique

Abstract: To screen specific serum biomarker for ankylosing spondylitis (AS) using a phage random peptide library. A phage random peptide library of random peptide 12-mers was immunoscreened with purified immunoglobulin (Ig) G from sera of AS patients. Positive clones obtained after three rounds of biopanning were detected with ELISA and sequenced. Reaction of the screened positive clones with sera from AS patients, systemic lupus erythematosus (SLE) patients, rheumatoid arthritis (RA) patients, osteoarthritis (OA) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Phage display technology was originally developed to map epitope-binding sites of antibodies by panning phage peptide libraries on immobilized immunoglobulins [8][10]. It involves specific screening and affinity selection of a certain phage displaying peptide that is ligand for particular proteins.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Phage display technology was originally developed to map epitope-binding sites of antibodies by panning phage peptide libraries on immobilized immunoglobulins [8][10]. It involves specific screening and affinity selection of a certain phage displaying peptide that is ligand for particular proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A major advantage of this technology is the extensive control of selection conditions, which allows preservation of the three-dimensional structure of peptides [14], [15]. Previous studies have used phage display peptide libraries to identify candidate biomarkers for diseases [8], [12]. Wang et al identified a mimic peptide as a potential biomarker of ankylosing spondylitis using a phage display peptide library [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations